Reorientation Of Halal Literacy Education Development in The Curriculum of Islamic Educational Institutions: An Alternative Concept - Kurahman, Opik Taupik; Priatna, Tedi; Cahyanto, Tri (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Law of the Republic of Indonesia Number 33 Year 2014 on Halal Product Warranty (JPH)  mandates the Government that the product circulating in Indonesia is guaranteed halal by the Halal Product Security Organizing Body (BPJPH). Public participation is required in halal product socialization and monitoring. Socialization and  education constitute an important task of education institution including madrasah. It is necessary for madrasah as a formal educational institution with Islamic characteristics to enhance its role in disseminating halal product so that students have better awareness on the importance of halal thayyiban products. The socialization and education of halal products will contribute to achieve one of the national educational goals in developing learners’ potentials so that they become the people imbued with human values who are faithful and pious to one and only God; who possess morals and noble character; who are healthy, knowledgeable, competent, creative, independent; and as citizens, are democratic and responsible. To meet the goal, madrasah must respond and play an active role in solving the problems that occur in community, one of   which is related to halal product issue. This study is intended to analyze the significance of implementing Halal Education in madrasah. This research applies literature study method. The research findings show that the issue of halal product does not have an adequate portion in Fiqh curriculum. The study of halal product in the curriculum is limited in doctrinaire perspective. The important issues on basic commodity, additives, production process, warehousing packing and halal product distribution need to be conveyed in madrasah education, considering that processed food for children in Indonesia is really complex and require a multi-disciplinary study